Effect of Green Accounting and CSR Disclosure on Financial Performance, Moderated by Institutional Ownership - Surahmat, Surahmat; Sailendra, Sailendra; Mulyadi, JMV (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
Financial performance is a description of the company's financial condition in a certain period that shows the company's ability to manage its resources. This study aims to analyze the effect of green accounting and CSR disclosure on financial performance, moderated by institutional ownership in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 - 2023. Financial performance projected by Return on assets (ROA). This test uses 50 samples of company data using purposive sampling method. Data analysis method using multiple linear regression. The results showed that green accounting which is proxied with Public Disclosure Program for Environmental Compliance (PROPER) predicate has a negative and significant effect on financial performance. CSR disclosure has a positive effect on financial performance. Institutional ownership moderates the influence of green accounting on financial performance and a negative moderator in the relationship between CSR disclosure and financial performance.